UPAYA MENINGKATKAN KEMAMPUAN MENGUNGKAPKAN PENDAPAT MELALUI PEMBERIAN LAYANAN INFORMASI MATERI POLA HIDUP SEHAT PADA SISWA SMP - Farida Nur Siregar; Fauziah Rasyid (Jurnal Dedikasi Pendidikan, 2021)
This study aims to improve the ability to express opinions through information services for class VII-1 students of SMP Negeri 2 Deli Tua for the 2017/2018 academic year. This research is a classroom action research which consists of four stages, namely planning, implementation, observation and reflection. This classroom action research was carried out in two cycles, the first cycle consisted of two meetings and the second cycle was carried out with one meeting. This research was conducted at SMP Negeri 2 Deli Tua. The subjects in this study were students of class VII-1, totaling 32 people. The data collection tool used is an observation sheet designed to measure students' ability to express opinions. The results of this study are a decrease in student truancy behavior and an increase in students' ability to express opinions. In the first cycle there was an increase in the ability to express students' opinions using information services, namely from 0% to 31% including in the low category. Furthermore, in the second cycle there was an increase of 76% and was included in the high category.